Formulasi Sediaan Liniment Aromaterapi dari Minyak Atsiri Bunga Kenanga (Cananga odorata): Formulation of Liniment Aromaterapy of Essential Oil Cananga Flower (Cananga odorata) - Ragil Sekar Ayuni; Dewi Rahmawati; Niken Indriyanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Cananga essential oil has potential as an antidepressant and a relaxant for the nervous system, containing a compound, namely linalool from the monoterpene. The innovation of topical pharmacy preparations with the active ingredient of cananga essential oil is a useful. The purpose of this study was to formulate cananga essential oil with concentrations used of 1%, 2% and 4%. The results showed that formulas I, II and III had met the physical quality evaluation. The results of the organoleptic test of the three formulations were in the form of a liquid, a characteristic odor of cananga flower along with eucalyptus oleum and a light yellow color. The results of the pH stability test obtained an average of 4.2 formulations, 4.9 formulations II and 5 formulations III. The homogeneity test results from formulations I, II and III obtained homogeneous results. The results of the anti-irritation test of formulations I, II and III did not cause irritation. The overall results of the preference test showed that the panelists preferred the liniment preparation at a concentration of 4%. Concluded that the formulation of liniment with the active ingredient of cananga essential oil produced preparations that met the physical characteristics and hedonic tests.